Understanding of the significance and health implications of asplenia in a cohort of patients with haemaglobinopathy: possible benefits of a spleen registry. Issue 8 (14th September 2018) - Premawardena, Chamath; Bowden, Donald; Kaplan, Zane; Dendle, Claire; Woolley, Ian John
ABSTRACT: Objectives: Asplenia and hyposplenism carry a significant risk of ongoing morbidity and mortality which can be reduced by education, vaccination and antibiotic use. We aimed to assess education and other methods of prevention in a cohort of patients with haemoglobinopathy in a tertiary referral centre, which also had access to a post-splenectomy registry created to reduce post-splenectomy infection risk. Methods: A standardized questionnaire was used on patients who attended the service for regular therapy. Patients were also asked about standard post-splenectomy preventive therapies including antibiotics and vaccinations. Results: There were 49 patients who had either had a splenectomy or knew their spleen to be non-functional. Of these, nearly half knew themselves to be on the Victorian Spleen Registry (51.0%). The median knowledge score was 12 (range 4–17) out of a possible 18. Most significantly the benefits of the registry were not seen in terms of knowledge but in delivery of recommended vaccines and the use of a medical alert card. Conclusion: This study examined knowledge and attitudes about splenectomy in a cohort of haemoglobinopathy patients in an Australian tertiary referral centre. The majority had good or fair knowledge with a strong association of some elements of post-splenectomy care with being placed on a spleen registry and having received targeted education. Implementation of systematic approaches by medical staff is likely to be the main benefit of a clinical registry approach in this setting.